Families: difficult to speak about? - Tarja Pösö (Scottish Journal of Residential Child Care)
While conducting a study on Finnish reform schools, remarks concerning the concept of family in relation to the young residents left me feeling uneasy. Family, in that particular context, seemed to be an issue of silence, where young people found difficulty in finding the words to express their ideas. Alternatively, the concept of family was limited to mainly legal definitions used by the professionals.